Temporal and spatial patterns of PM10 concentrations at an urban area - Pires, JCM (2013)
Particulate matter is one of the most important air pollutants that negatively influence human health in Europe. They are emitted by both natural (volcanic eruptions, seismic activity and forest fires) and anthropogenic sources (all types of man-made combustion and some industrial processes). Long exposure to PM10 and to PM2.5 (particles with an aerodynamic diameter smaller than 10 and 2.5 m, respectively) has been associated with respiratory and cardiovascular diseases. Air quality is strongly dependent on weather and, therefore, sensitive to climate change. Consequently, temporal and spatial patterns of air pollution are not only dependent on emission changes. The changes in the boundary layer height, relative humidity, temperature, solar radiation, wind speed and precipitation may be responsible for significant differences in air pollutant concentration patterns. Thus, this chapter aims to evaluate temporal and spatial patterns of PM10 concentrations at an urban area through the application of principal component analysis (PCA). It was applied to air quality data collected in the Air Quality Monitoring Network of Oporto Metropolitan Area during the period from 2006 to 2010. The monitored region presented high PM10 concentrations (with several exceedances to European Union standard limits); however, they presented a decreasing tendency. PCA identified seven to nine PM10 pollution patterns. Two monitoring sites often presented similar air pollution pattern. Analysing the annual average profile, PM10 concentrations were higher during night time in winter period. This phenomenon is justified by the daily and seasonal variation of atmospheric boundary layer height, which influences the mixing of air pollutants.